DETERMINATION OF PROFESSIONALISM AND TRANSPARENCY AND ITS IMPLICATIONS FOR THE FINANCIAL PERFORMANCE OF ZAKAT INSTITUTIONS - Nasri, Rifzaldi; Aeni, Nur; Haque-Fawzi, Marissa Grace (Journal of Islamic Monetary Economics and Finance, 2019)
The objective of this study is to determine the influence of the professionalism andtransparency of zakat management on financial performance, especially in the case ofthe Amil Zakat Institution of Daarut Tauhid Peduli Jabodetabek. The method used inthe research is SEM (structural equation modeling) using AMOS, with 156 respondents.The results show that: (1) professionalism has a negative and insignificant impact on thetransparency of zakat management; (2) professionalism has a positive and significantimpact on financial performance; and (3) the transparency of zakat management haspositive and significant impacts on financial performance. Moreover, the indicatorsof competence have the highest loading factors of professionalism; the indicator ofinformation on fund management has the highest loading factors of transparency;while the indictor of measurement of economics has the highest loading factor offinancial performance. To sum up, this research suggests that zakat institutions shouldimprove their transparency and professionalism in order to improve their financialperformance in the future.